Applying GIS Concept In Creating Info Kiosk: Medical Centre - Abd Halim, Maya Shahida (Universiti Teknologi Petronas, 2006)
This project dissertation report was entitled Applying GIS Concept in Creating Info Kiosk: Medical Centre, The system should be implemented as a server side client method. It consists of graphical representation of informative and knowledge about medical centerallocated aroundMalaccathat coveredalmost major area around the state. The system concludes some of the basic point or base station for mobile interaction among wireless connection throughout three different coverage areas. They're also some useful query for finding the best route and few other queries in term of medical information and allocation of places regard to map that was illustrated. This system will help people to make their life become easier in doing their routine job. The system helps people by using devices to guide them to find the way to the location or destination that they want to go. It will be control by the central system that remotely to the mapdatabase server and required the combination of various kind of technology like the integrated wireless LAN system, geographical information system (GIS), and satellite positioning technology. The system will respond to instructions verbally so that the people can be easily finding his/her way to the hospital. It keeps track of the user location while giving directions to a destination and may even warn the user against veering off a sidewalk or stepping into a road.